Reinventing the organization : how companies can deliver radically greater value in fast-changing markets - Yeung, Arthur K.; Ulrich, David, 1953- (Boston, Massachusetts : Harvard Business Review Press, 2019)
Leaders know that as markets and strategies change, organizations must evolve. The traditional hierarchical organization has long been under fire, resulting in numerous new organizational experiments. Leaders need a synthesis of what we know about these emerging models, along with an integrated perspective that can guide practice. What is the new organization, and how does it work? Arthur Yeung and Dave Ulrich provide that much-needed synthesis and offer leaders a practical, integrated framework for reinventing the organization. They explain how to build a new kind of organization (a "market-oriented ecosystem") that responds to changing market opportunities with speed and scale. While other books address individual pieces of the puzzle, Reinventing the Organization looks at all the decisions leaders need to make--choosing the right strategies, capabilities, structure, culture, management tools, and leadership to deliver radically greater value in fast-moving markets.--
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on September 24, 2019).
Added to collection customer.56279.3
Keywords: Business enterprises; Strategic planning; Organizational effectiveness; Organizational behavior; Success in business; Business enterprises; Organizational behavior; Organizational effectiveness; Strategic planning; Success in business; elektronické knihy; electronic books